The mmpL3 interactome reveals a complex crosstalk between cell envelope biosynthesis and cell elongation and division in mycobacteria - Belardinelli, Juan Manuel, author; Stevens, Casey M., author; Li, Wei, author; Tan, Yong Zi, author; Jones, Victoria, author; Mancia, Filippo, author; Zgurskaya, Helen I., author; Jackson, Mary, author; Springer Nature Publishing, publisher (Colorado State University. Libraries, 2019)
Integral membrane transporters of the Mycobacterial Membrane Protein Large (MmpL) family and their interactome play important roles in the synthesis and export of mycobacterial outer membrane lipids. Despite the current interest in the mycolic acid transporter, MmpL3, from the perspective of drug discovery, the nature and biological significance of its interactome remain largely unknown. We here report on a genome-wide screening by two-hybrid system for MmpL3 binding partners. While a surprisingly low number of proteins involved in mycolic acid biosynthesis was found to interact with MmpL3, numerous enzymes and transporters participating in the biogenesis of peptidoglycan, arabinogalactan and lipoglycans, and the cell division regulatory protein, CrgA, were identified among the hits. Surface plasmon resonance and co-immunoprecipitation independently confirmed physical interactions for three proteins in vitro and/or in vivo. Results are in line with the focal localization of MmpL3 at the poles and septum of actively-growing bacilli where the synthesis of all major constituents of the cell wall core are known to occur, and are further suggestive of a role for MmpL3 in the coordination of new cell wall deposition during cell septation and elongation. This novel aspect of the physiology of MmpL3 may contribute to the extreme vulnerability and high therapeutic potential of this transporter.